High-risk prostate cancer: a disease of genomic instability - Tapia-Laliena, María Angeles; Korzeniewski, Nina; Hohenfellner, Markus; Duensing, Stefan (Urologic oncology, 2014)
Objectives - In this review, we will discuss the latest advances in our understanding of the relationship between the cellular DNA damage response and genomic instability in prostate cancer and the emerging possibilities to exploit these aberrations as prognostic biomarkers and guides for personalized patient management. - Methods - Important findings related to genomic instability in prostate cancer were retrieved from the literature and combined with our own results and a translational perspective. - Results - Prostate cancer is characterized by a highly altered genomic landscape with a wide spectrum of genomic alterations, including somatic mutations, copy number alterations (CNAs), gene fusions, complex chromosomal rearrangements, and aneuploidy. In addition, massive DNA damaging events, including chromothripsis and chromoplexy, which can lead to extensive genomic insults in a single step, have been identified. A number of these genomic aberrations have been found to provide prognostic information and can therefore help to identify high-risk patients. In addition, defects in the DNA damage checkpoint and repair machinery can potentially be harnessed for therapeutic purposes. - Conclusions - Genomic instability plays a crucial role in the malignant progression of prostate cancer and can be exploited for the development of novel prognostic biomarkers and innovative therapies.